Perceptions of community and family level IDU and HIV related stigma, disclosure decisions and experiences with layered stigma among HIV positive injection drug users in Vietnam - Rudolph, A.E. (2011)
This paper explores how perceived stigma and layered stigma related to injection drug use and being HIV positive influence the decision to disclose one’s HIV status to family and community and experiences with stigma following disclosure among a population of HIV positive male injection drug users (IDUs) in Thai Nguyen, Vietnam. In qualitative interviews conducted between 2007 and 2008, 25 HIV positive male IDUs described layered stigma in their community but an absence of layered stigma within their families. These findings suggest the importance of community level HIV prevention interventions that counter stigma and support families caring for HIV positive relatives.